KEPUTUSAN PEMBELIAN ULANG DITINJAU DARI EXPERIENTAL MARKETING DAN KEPUASAN PELANGGAN PADA THE HIDDEN PLACE SURAKARTA - Adinia Intan Pratiwi; Siti Maryam; Ratna Damayanti (JURNAL ILMIAH EDUNOMIKA, 2020)
This study aims to determine the effect of repurchase decisions in terms of experiential marketing and customer satisfaction at The Hidden Place Surakarta. This type of research is descriptive quantitative. This study uses primary data collected using a questionnaire as a research instrument. The sample research method used was non probability sampling with purposive sampling technique. The respondents of this study were consumers who made at least two purchases. respondents who used were 100 respondents. The data analysis technique used is path analysis. The results of the study can be concluded that experiential marketing has a positive and significant effect on repurchase decisions, experiential marketing has a positive and significant effect on customer satisfaction, customer satisfaction has a positive and significant effect on repurchase decisions, experiential marketing has a positive and significant effect on repurchase decisions through customer satisfaction. Keywords: Experiential marketing, customer satisfaction, repurchase decisions